2013
DOI: 10.1103/physrevlett.110.090402
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg Polaritons in a Cavity: A Superradiant Solid

Abstract: We study an optical cavity coupled to a lattice of Rydberg atoms, which can be represented by a generalized Dicke model. We show that the competition between the atom-atom interaction and atom-light coupling induces a rich phase diagram. A novel superradiant solid (SRS) phase is found, where both the superradiance and crystalline orders coexist. Different from the normal second order superradiance transition, here both the solid-1/2 and SRS to SR phase transitions are first order. These results are confirmed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…This agreement order by order in the hopping expansion is insofar surprising as the strong-coupling method yields reliable results for low dimensions, whereas EPLT has shown to be most accurate for high dimensions [37]. In addition we have obtained high-precision QMC results from developing an algorithm on the basis of a stochastic series expansion [52][53][54][55][56]. In order to get the high accuracy quantum phase diagram in the thermodynamic limit from QMC, we performed a finite-size scaling with the lattice sizes N = 8 × 8, 10 × 10, and 12 × 12 at the temperature T = U/(20N ).…”
Section: Higher Order and Numerical Resultsmentioning
confidence: 81%
“…This agreement order by order in the hopping expansion is insofar surprising as the strong-coupling method yields reliable results for low dimensions, whereas EPLT has shown to be most accurate for high dimensions [37]. In addition we have obtained high-precision QMC results from developing an algorithm on the basis of a stochastic series expansion [52][53][54][55][56]. In order to get the high accuracy quantum phase diagram in the thermodynamic limit from QMC, we performed a finite-size scaling with the lattice sizes N = 8 × 8, 10 × 10, and 12 × 12 at the temperature T = U/(20N ).…”
Section: Higher Order and Numerical Resultsmentioning
confidence: 81%
“…Hence we can obtain a high fidelity of two-atom entanglement 99.14%. For the second scheme based on quantum feedback control, the experimentally available coupling strength between atom and cavity g = 2π × 14.4 MHz and the cavity decaying rate κ = 2π × 0.66 MHz should also be taken into account [46][47][48]. In this case, we choose ∆ p = 2π×1.44 GHz and Ω b = g in order to gain a fidelity 98.95% at a short time about t = 50/g eff ≈ 55.26 µs.…”
Section: Generalization To Three-atom Entanglementmentioning
confidence: 99%
“…The optical nonlinearity has been experimentally explored with strongly interacting Rydberg atoms in cavities [12], even at the level of individual * huaizhi.wu@fzu.edu.cn † zbyang@fzu.edu.cn quanta [13]. Moreover, Zhang et al have shown that coupling of optical cavity to a lattice of Rydberg atoms can be described by the Dicke model, the competition between the atom-atom interaction and atom-light coupling can induce a novel superradiant solid phase [9]. On the other hand, rich quantum dynamics has been found in the coupling of the coupled cavities with neutral atoms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-finesse optical cavity has been used to couple Rydberg atoms with quantized cavity modes, which presents potential applications in studying photon nonlinearity and many-body physics [8][9][10]. Neutral atoms excited by laser beams and the cavity field to high-lying Rydberg states can interact through strong and long-range dipole-dipole or van der Waals interaction [11].…”
Section: Introductionmentioning
confidence: 99%